Size of corpora and collocations: The case of Russian - Maria Khokhlova; Vladimir Benko (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave)
With the arrival of information technologies to linguistics, compiling a large corpus of data, and of web texts in particular, has now become a mere technical matter. These new opportunities have revived the question of corpus volume that can be formulated in the following way: are larger corpora better for linguistic research or, more precisely, do lexicographers need to analyze bigger amounts of collocations? The paper deals with experiments on collocation identification in low-frequency lexis using corpora of different volumes (1 million, 10 million, 100 million and 1.2 billion words). We have selected low-frequency adjectives, nouns and verbs in the Russian Frequency Dictionary and tested the following hypotheses: 1) collocations in low-frequency lexis are better represented by larger corpora; 2) frequent collocations presented in dictionaries have low occurrences in small corpora; 3) statistical measures for collocation extraction behave differently in corpora of different volumes. The results prove the fact that corpora of under 100 M are not representative enough to study collocations, especially those with nouns and verbs. MI and Dice tend to extract less reliable collocations as the corpus volume extends, whereas t-score and Fisher’s exact test demonstrate better results for larger corpora.